Combinatorial Rules Approach to Improve Priority Rules Scheduler in Grid Computing Environment - Zafril Rizal, M Azmi; Herawan, Tutut; Kamalrulnizam, Abu Bakar; Abdul Hanan, Abdullah; Mohd Shahir, Shamsir (2012)
This paper proposed a set of Combinatorial Rules (CR) based on five traditional Priority Rules (PR) algorithms. The proposed CR aims to improve the PR by balancing the tradeoff between five performance metrics. Experimental results shows that the proposed algorithms are much better compared to the PR and well known SJFR-LJFR.